Technical Features and Development Trends of Liquid Air Energy Storage - Wang Yuting (E3S Web of Conferences)
Liquid Air Energy storage (LAES), as an innovative approach to energy storage, utilizes the cryogenic properties of air to provide long duration of energy storage. Through the process of cooling air and storing it in liquid form, LAES systems can release energy when in need, expanding the air and driving turbines to generate electricity. This paper assesses LAES technology’s potential, especially in grid balancing and as a back energy storage, noting its compatibility with renewable sources with a discontinuous energy supply, like wind and solar. While LAES systems provide high energy density, long operational lifetimes, and minimal environmental impact, they face challenges that include low round-trip efficiency, scalability issues, and high capital costs. Current research focuses on improving efficiency through thermal storage integration, reducing material costs, and developing hybrid systems to enhance LAES performance. Future advancements in thermal management and modular designs are expected to address existing challenges, placing LAES as a feasible solution for grid stability and renewable energy integration.